TO STUDY THE EFFECT OF “VASAADI KASHAYA” IN THE MANAGEMENT OF KAMALA WITH SPECIAL REFERENCE TO HYPERBILIRUBINAEMIA (AYUSHDHARA, 2018)
The incidence of Kamala is very common due to life style, food habits and sanitation (water pollution and contaminated food) etc. as there is no conventional therapy available in modern sciences, so people are having affinity towards Ayurveda. This makes it necessary to work out in this issue, by providing safe effective and affordable treatment. Ayurveda provides cure of the disease on the basis of proper flow of Pittadosha in Koshtha in case of Shakhashrit kamala. Pittashamak, Yakrut uttejak, Yakrut shodhana to normal flow of bile from liver in case of Bahupitta kamala. Hyperbilirubinaemia is a condition where there is yellow appearance of skin, sclera and mucous membrane resulting from an increase bilirubin concentration in the body fluids, mostly explained as jaundice which resemble the sign “Haridratwakanakhannana, Haridra-Netra-mutra ”explained in the Kamala in Charak chikitsa sthana (16/35and126). The present study was planned to evaluate the effect of Vasadi kashaya on Kamala w. s. r. to Hyperbilirubinemia. Total 30 patients attending the OPD and IPD of R. A. Podar Ayurvedic Hospital Mumbai were randomly selected. After classical formulation Vasadi Kashaya was given for 3 weeks to these patients. Significant improvement was observed in the symptoms of Kamala.